Technical report on E-PICSA training for senior lead farmers in Eastern Province - Gamoyo, Majambo; Koech, Grace; Chilambe, Pedro; Ghosh, Aniruddha; Wanjau, Agnes (2024)
Agriculture is the backbone of the economy for many countries and region including Sub-Saharan, supporting 67% of the labor force and contributing 17% of the region’s GDP. Yet, climate variability, including irregular rainfall and severe drought, seriously threatens the sector, especially for smallholder farmers who depend on rainfed farming. During the 2023/2024 season, Zambia faced one of its worst droughts, driven by a strong El Nino, which heavily impacted maize production and highlighted the urgent need for resilient farming approaches. To address these challenges, the Alliance of Bioversity Internation and CIAT, with Community Markets for Conservation (COMACO), facilitated training 103 senior lead farmers in the Electronic Participatory Integrated Climate Services for Agriculture (E-PISCA) tool. This tool equips them with precise climate information and participatory decision-making resources, fostering climate-resilient practices critical for sustaining livelihoods amid climate challenges.